Discrimination of offspring by indirect recognition in an egg-feeding dendrobatid frog, Oophaga pumilio - Stynoski, Jennifer Lynn (2009)
Offspring discrimination, the differential treatment of offspring and unrelated young, functions in numerous animal taxa to ensure that vital and costly parental care behaviours are appropriately directed. Discrimination can be facilitated either by direct (phenotypic) recognition of offspring or by indirect (nonphenotypic) recognition of offspring location. Offspring discrimination and recognition mechanisms have not been identified in an amphibian. In the strawberry poison frog, Oophaga pumilio, a dendrobatid frog with obligatory maternal provisioning behaviour, I tested whether mothers discriminate between offspring and unrelated young, whether they use direct or indirect recognition cues, and whether prior parental investment plays a contextual role in the differential treatment of young. Mother frogs utilized tadpole-rearing cups attached to tree trunks in wet tropical forest. After manipulating the identity, location and/or age of tadpoles in cups, I determined whether maternal provisioning behaviour was maintained by measuring tadpole growth and development. Mothers provisioned young regardless of tadpole identity, but were sensitive to location and did not provision tadpoles that were moved 2 cm to an adjacent cup. When given a choice between related and unrelated tadpoles in originally chosen or adjacent cups, mothers discriminated by location, but not by relatedness. Maternal provisioning behaviour persisted when a tadpole provisioned for 10 days was replaced with either an age-matched or newly hatched unrelated tadpole, so direct offspring recognition does not appear to be dependent on prior parental investment. Together, these results provide strong evidence that mother O. pumilio use indirect recognition cues to discriminate between offspring and unrelated offspring.